Trade Agreements and Indonesia’s Export Intensity across Partner Countries: Perjanjian Perdagangan dan Intensitas Ekspor Indonesia pada Berbagai Mitra Dagang - Nurkhamid, Muh; Kusumawati, Rahayu (Indonesian Journal of Innovation Studies, 2025)
Background: Trade agreements play an increasingly central role in shaping Indonesia’s export participation within a global environment marked by structural disparities and non-tariff constraints. Specific background: Although Indonesia has entered numerous trade agreements, the degree to which these agreements correspond with higher export intensity varies substantially across partner countries. Knowledge gap: Prior studies predominantly examine export values or volumes, while limited research assesses export intensity using a structural indicator that captures the depth of bilateral trade preferences. Aim: This study analyzes Indonesia’s export intensity across partner countries with and without trade agreements using the Trade Intensity Index for the period 2010–2023. Results: Feasible Generalized Least Squares estimation shows that trade agreements are consistently associated with higher export intensity, whereas domestic and partner economic size correspond with lower relative intensity. Non-tariff barriers remain the strongest limiting factor, while tariffs and real bilateral exchange rates do not show statistical relevance. Economic distance aligns with higher export intensity, reflecting complementarities with high-demand economies. Novelty: The study integrates structural, macroeconomic, and policy-related variables within an intensity-based framework rather than focusing solely on export levels. Implications: Findings highlight the importance of reducing non-tariff constraints and strengthening firm capability so that trade agreements can support deeper export engagement across partner countries. Highlights: Export intensity is generally higher among Indonesia’s partner countries with formal trade agreements. Non-tariff barriers remain the strongest factor limiting Indonesia’s export intensity across partners. Economic distance aligns with stronger export intensity due to structural complementarities with larger economies. Keywords Free Trade Agreement, Trade Intensity Index, Non-Tariff Barriers, Panel Data, Gravity Model